Buyer-supplier contract length and the innovation of supplier firms - Nguyen Thanh Liem; Nguyen Vinh Khuong; Nguyen Thi Canh (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The relationship with customers has important implications for operating decisions as well as firm performance. One important aspect of the supplier-buyer relationship is the contract duration, and how this factor is likely to affect firm investments has been under-researched. This study aims to investigate whether corporate innovation is linked to the maturity of contracts between suppliers and buyers. Using a sample of 1516 manufacturing firms in Vietnam for the period of 2014 to 2018, we find that longer-term contracts are positively related to firm propensity of innovation. However, only contracts with foreign purchasers have this characteristic, confirming the supportive role of foreign partners in uplifting the technology for domestic suppliers in a developing country. Interestingly, longer contracts do not tend to facilitate firm innovation or raise the aimed level of newness for firms with very long contracts compared with those that have short-term contracts. This is consistent with the agency cost theory. These findings are robust to different specifications and econometric approaches. Based on the findings, implications are provided to manage the relationship with customers more efficiently.
Keywords: 650; agency cost theory; contract length; firm innovation; manufacturing firms